Current Tropical Medicine Reports - Bottazzi, Maria Elena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Current Tropical Medicine Reports provides expert views on recent advances in the field of tropical medicine in a clear and readable form. This journal offers reviews by domestic and international contributors that highlight the most important, recent papers and findings related to this specific field. We accomplish this by appointing renowned leaders in major tropical medicine subject areas to select topics addressing virology, bacteriology, parasitology, entomology, immunology, cell and molecular biology, epidemiology, ecology, behavioral science and clinical medicine for review by experts who assess the latest developments and highlight significant papers published over the last few years on their topics. These review articles also stress recently published papers of importance in the references, which are accompanied by annotations explaining their importance. In addition to these Section Editors, our international Editorial Board ensures our journal upholds its standards.
Keywords: Parasitology; Infectious diseases; Tropical medicine; Behavioral sciences; Tropical Medicine; Parasitology; Behavioral Sciences; Infectious Diseases